Enforcement of State Law by the Republic of Indonesia Attorney General's Office in the Perspective of Law Number 16 of 2004 - Wijaya, Armen; Santiago, Faisal (Green Publisher Indonesia, 2024)
The Republic of Indonesia is a country with a constitutional system that is governed by the Indonesian Constitution. It is an independent and effective law enforcement agency in Indonesia. This paper aims to explore the enforcement of state law by the Prosecutor's Office of Indonesia (Kejaksaan RI) in the perspective of Law Number 16 of 2004. It focuses on the mechanisms, practices, and effectiveness of this enforcement from a legal and procedural standpoint. The research may offer insights into the interpretation and application of this law, identify challenges, and suggest potential improvements or reforms in the enforcement process. It provides a solid legal foundation for the Attorney General's office of Indonesia to carry out its duties as a policing in upholding justice and legal sovereignty in Indonesia's established framework. It emphasizes the crucial role of the Penal Service of Indonesia in constitutional law enforcement, including prosecuting crimes that harm the interests of the state or the public. Ensuring constitutional law enforcement is crucial for maintaining legal stability, eradicating corruption, improving governance, and strengthening public trust. Indonesia can achieve effective enforcement through strengthening regulations, coordination between legal institutions, and government, and by enhancing capacity and resources through training, education, professional development, interagency cooperation, and transparency and accountability.